1986
DOI: 10.1111/j.1745-4603.1986.tb00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Force‐deformation Characteristics of Artificial and Several Natural Foods for Chewing Experiments

Abstract: The masticatory performance of an individual has been quantified by determining the particle sizes of the comminuted food. Optosil, a silicon rubber, has been used as an artificial test food in clinical studies, because it has reproducible textural properties. A comparison between Optosil and several natural foods was made by measuring textural properties of Optosil, turnip, carrot, Gouda cheese and peanut. Several types of probes were used to imitate the cusp form of the teeth. Force‐deformation plots reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…However, the pattern of this mediolateral motion has not been established (17). The frequent bilateral pattern found in the present study may also be a response for the great effort needed to crush the artificial chewing material used, once it is found to be of high deformation resistance (19). Under the tested conditions, it can be concluded that masticatory performance is not correlated to a defined mandibular movement pattern, which did not differ between bilateral and unilateral chewers.…”
Section: Discussionmentioning
confidence: 55%
“…However, the pattern of this mediolateral motion has not been established (17). The frequent bilateral pattern found in the present study may also be a response for the great effort needed to crush the artificial chewing material used, once it is found to be of high deformation resistance (19). Under the tested conditions, it can be concluded that masticatory performance is not correlated to a defined mandibular movement pattern, which did not differ between bilateral and unilateral chewers.…”
Section: Discussionmentioning
confidence: 55%
“…5 and 6) when Optosil cubes with an edge size of 8.0 or 9.6 mm were used. Most likely, the jaw was then decelerated by the sudden resistance of the relatively large food particles of Optosil, a very firm test food (Olthoff et al, 1986). The deceleration could also be observed directly from the velocity signal ( Fig.…”
Section: Discussionmentioning
confidence: 94%
“…The electromyographic recordings were analyzed while the artificial food, which was based on the composition of Optocal ATF [8] , was being chewed. The food was fragmented, observing the recommendations of Slagter et al [9] .…”
Section: Methodsmentioning
confidence: 99%